Assessment of Personality Traits Influencing the Performance of Men in Team Sports in Terms of the Big Five - Piepiora, Paweł (Frontiers in Psychology, 2021)
The purpose of this article is to define the perspective from which a coach should analyse and evaluate personality traits that influence sports performance in team sports. The subjects of the research are Polish players (N = 300) in the senior age (20-29 years) from 10 team sports (each n = 30). Then, a sample of champions (n = 13) was selected from the study population. The Big Five model was used to examine their personality. For this purpose, the NEO-FFI questionnaire was used. Statistical analyses were performed with the IBM SPSS Statistics software, version 25. There were statistically significant differences between team sports in four personality traits: neuroticism, extraversion, agreeableness and conscientiousness. On the other hand, champions of team sports were characterized by a lower level of neuroticism, a higher level of extraversion and openness to experiences in relation to other sportsmen. It was confirmed that personality traits distribution levels are dependent on the sport discipline. An important role must be assigned to those mental training techniques that favour emotional balance, team communication and tactical thinking skills, and are manifested in triggering start-up readiness. Public Significance Statements They can constitute the basis for the development of appropriate practical directives, important in the sports training of high-class players. It is suggested that in the sports selection of high-class players to the national team, the first verification stage should be the distribution level of personality traits. Candidates meeting the criteria of low neuroticism, high extraversion, and openness to experience may be the desired individuals at the mental selection stage. Only in the second stage, physical criteria should be taken into account, i.e. somatic build and motor, technical and tactical predispositions as well as the achievements of the contenders.